Environmental factors influencing age at natural menopause in women - Rumianowski, Bogdan; Brodowska, Agnieszka; Karakiewicz, Beata; Grochans, Elżbieta; Ryterska, Karina; Laszczyńska, Maria (Menopause Review/Przegląd Menopauzalny, 2012)
Menopause means a definitive end of the generative ovarian function and mostly occurs in women aged 40-58. It is well-known that the sooner it occurs the more serious consequences may result, even in the case of early menopausal hormone therapy. The most serious short-term consequences of menopause are menopausal symptoms (depression, hot flushes, sleep disorders, loss of libido), while long-term estrogen deficiency leads to osteoporosis, cardiovascular system diseases, depression, neurodegenerative diseases, urogenital area atrophy, skin and sense organ disorders. Therefore, an important task is to select women at risk of premature termination of the ovarian function. An important issue thus appears to be identification of factors influencing the age of the last natural menstrual period. Analysis of heritability results has brought the conclusion that the age of menopause is a multifactorial trait. The proportion of the impact of environmental and genetic factors, however, was not precisely estimated. Among environmental determinants the influence of many factors is being considered, including reproductive factors (related to the reproductive period), such as age of menarche, number of pregnancies and children, socio-economic factors, such as education, economic status, health determinants, such as the use of oral contraceptives or lifestyle-related factors, such as physical activity and the use of stimulants. Among the genetic factors, a genetic polymorphism of genes encoding enzymes of the estrogen biosynthesis pathway and other independent markers scattered throughout the genome (linkage studies and genome-wide association studies – GWAS) is taken into consideration.